Ciberativismo do consumidor: retaliação e vingança em comunidades virtuais antimarca - Albuquerque, Fábio Manoel Fernandes de (2010)
The advent of computer-mediated communication and digital social networks tools in cyberspace, has modified the form of social participation, expanded the influences in the building of consumption experiences and enhanced the power of consumers in contemporary society. Unhappy consumers start to gather in virtual communities and forums to denounce, protest and publicly repudiate failures and injustices in relations of consumption. Marketing literature has shortly investigated antibranding virtual communities, which are freely formed on social networking websites and attract consumers who have motivations against brands, products and services. This study sought to understand the causal relationships between retaliation, revenge and anticonsumption cyberactivism in virtual antibranding communities. The adopted method in empirical research was netnography, which consists of an adaptation of the ethnography from cultural anthropology applied to the study of online relationship networks, thus providing, in particular, qualitative and interpretive research of the cultural and symbolic aspects of consumption patterns shared by a group of people who gather in cyberspace. As specific cases of analysis, we chose to study five antibranding communities on the popular virtual-social relationship tool Orkut. From the analysis of the content of reports and conversations between members in this type of social computer-mediated aggregation, we identified four motivating factors of retaliation and revenge (service failure, failure in recovering customers, perceived injustice post-complaint and costs and losses), four retaliation behaviors (consumption prevention, personal attack, threat and cynicism), five revenge behaviors (avoidance of the brand, betrayal, boycott, causing losses and activism); four motivating factors of anti-consumerism cyberactivism (concerning about the overall impact of consumption, resistance to the exploitation of consumption, concerning about voluntary simplicity, and rejection of the brand); and two factors that characterizes the anti-consumption counter-cyberactivism in virtual antibranding communities (defense of the target-brand and dissociation between the consumption of target-brand and cultural alienation), which validates and extends theoretical models established in the literature about consumer behavior. The study reveals that virtual antibranding communities allow consumers to assume roles of social consumption activists, or antibranding and anti-consumerism cyberactivists. Finally, the results suggest the existence of causal and interdependent connections between retaliation, revenge and cyberactivism of consumers in antibranding virtual communities, constituting the anticonsumption as a link between the three constructs analyzed.